1982
DOI: 10.1007/bf03007740
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the caffeine skinned fibre tension (csft) test with the caffeine-halothane contracture (chc) test in the diagnosis of malignant hyperthermia

Abstract: We have compared and contrasted two diagnostic tests for Malignant Hyperthermia (MH) -the Caffeine-Halothane Contracture Test and the Caffeine Skinned Fibre Tension Test. Both tests show a strongly positive relationship both with the occurrence of MH reactions and with each other. The former test is more rapid and requires less skill. The latter test can be performed on much less muscle and permits storage of the muscle over prolonged periods of time. of muscle required was small. Moreover, fibres prepared fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1986
1986
2000
2000

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 22 publications
(1 reference statement)
0
5
0
Order By: Relevance
“…If the relevant target of caffeine action is the Ca2 +-ATPase [ 3 3 ] , it is possible that on account of the deficiency of this enzyme in type 2 fibers, the excessive caffeine sensitivity is attributable to type 1 fibers, which are known to be more sensitive to caffeine [ 3 ] . Since an , abnormally low caffeine-specific concentration in an in vitro contracture test usually correlates with predisposition to malignant hyperthermia reaction [2], appropriate anesthetic precautions appear to be advisable in Brody's disease.…”
Section: Discussionmentioning
confidence: 99%
“…If the relevant target of caffeine action is the Ca2 +-ATPase [ 3 3 ] , it is possible that on account of the deficiency of this enzyme in type 2 fibers, the excessive caffeine sensitivity is attributable to type 1 fibers, which are known to be more sensitive to caffeine [ 3 ] . Since an , abnormally low caffeine-specific concentration in an in vitro contracture test usually correlates with predisposition to malignant hyperthermia reaction [2], appropriate anesthetic precautions appear to be advisable in Brody's disease.…”
Section: Discussionmentioning
confidence: 99%
“…However, when the new version of the cutoff point (Ͼ0.5 g at 3% halothane, Ͼ0.3 g at 2 mM caffeine in the NAMHG protocol) was applied to our results, the accordance rate between the two CHCTs decreased to 83%. Several types of skinned-fiber tests for diagnosis of MH have been reported [19,20]. This is the test to determine the sensitivity of skinned fibers for contracture obtained by caffeine or halothane according to the same principle used to measure the threshold of contracture in CHCT.…”
Section: Discussionmentioning
confidence: 99%
“…This is the test to determine the sensitivity of skinned fibers for contracture obtained by caffeine or halothane according to the same principle used to measure the threshold of contracture in CHCT. One comparative study showed that the caffeine skinned fiber tension test showed a strongly positive relationship with CHCT, and the authors concluded that this test could be used as a complement test because of a decrease in the required sample size and a longer possible time period from biopsy to test, but not that the test could be used as a substitute for CHCT [19]. Using 50% glycerol-EGTA pretreated skinned fibers, Adnet et al showed a significantly higher sensitivity to caffeine in type I fibers (slow-twitch, slow oxidative) than in type II fibers (fast-twitch, fast glycolytic) from MHS and MH nonsusceptible patients [21].…”
Section: Discussionmentioning
confidence: 99%
“…Tests involving simultaneous exposure to both halothane and caffeine produce data which overlap between normal and known MHS patients [3]. Takagi and colleagues [12] have suggested the use of a single skinned muscle fibre test which seems to correlate with the muscle bundle test [13]. However, this method is difficult to perform and time consuming.…”
Section: Discussionmentioning
confidence: 99%